2011
DOI: 10.1007/s12010-011-9373-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Reducing Equivalent Generation for 1,3-Propanediol Production Through Cofermentation of Glycerol and Xylose by Klebsiella pneumoniae

Abstract: 1,3-Propanediol (1,3-PD) biosynthesis plays a key role in NADH consumption to regulate the intracellular reducing equivalent balance of Klebsiella pneumoniae. This study aimed to increase reducing equivalent for enhancing 1,3-PD production through cofermentation of glycerol and xylose. Adding xylose as cosubstrate resulted in more reducing equivalent generation and higher cell growth. In batch fermentation under microaerobic condition, the 1,3-PD concentration, conversion from glycerol, and biomass (OD(600)) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Many strategies based on adjusting the intracellular redox level to enhance bioproduct formation in K. pneumoniae have been reported . In the present study, inactivating NQOs either inhibited cell growth or increased the cellular NADH:NAD + ratio, depending on the NQOs inactivated.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Many strategies based on adjusting the intracellular redox level to enhance bioproduct formation in K. pneumoniae have been reported . In the present study, inactivating NQOs either inhibited cell growth or increased the cellular NADH:NAD + ratio, depending on the NQOs inactivated.…”
Section: Discussionmentioning
confidence: 60%
“…inactivated the ldhA gene, which is responsible for lactate formation, resulting in a slight increase in 1,3‐PD and substantial improvement in the production of 2,3‐BD . In addition, the amount of reducing equivalents in cells was increased by co‐fermentation of glycerol and xylose, resulting in an increase in 1,3‐PD formation .…”
Section: Introductionmentioning
confidence: 99%
“…There are many successful examples in the literature reporting cosubstrate fermentation to achieve better fermentation performance and to increase product yields. Adding sugars, mannitol, or hemicellulose hydrolysate as a cosubstrate to glycerol can significantly increase the yield of 1,3-propanediol production (31)(32)(33). Beet molasses added as a cosubstrate promoted 2,3-butanediol production from biodiesel derived glycerol (34).…”
Section: Discussionmentioning
confidence: 99%
“…Xylose is another abundant monosaccharide after glucose. It has been reported that xylose could be used as a cosubstrate to increase the production of 1,3-PD in K. pneumoniae from glycerol [8]. In Klebsiella, xylose is converted into xylulose by xylose isomerase (XylA) and then catalyzed into xylulose 5-phosphate by xylulokinase (XylB).…”
Section: Introductionmentioning
confidence: 99%